The lemon drop kid [videorecording (DVD)] - Lanfield, Sidney, 1898-1972; Hope, Bob, 1903-2003; Maxwell, Marilyn; Nolan, Lloyd; Darwell, Jane, 1880-1967; Frawley, William, 1887-1966; Runyon, Damon, 1880-1946 (Shout Factory, 2010)
A small-time con artist, nicknamed for his favorite candy, gets in over his head when he swindles a tough gangster out of some gambling profits. The Kid concocts a scheme to pay back the money by Christmas, by tricking his pals into dressing up as Santas and collecting money for a made-up charity.